First clinical isolation of an azole-resistant aspergillus fumigatus isolate harboring a TR46 Y121F T289A mutation in South America - Isla, Guillermina (2018)
One of the most recently described Aspergillus fumigatus CYP51Amediated azole resistance mechanisms is TR46 Y121F T289A. Clinical A. fumigatus strains harboring these substitutions have been reported worldwide, with the exception of South America. We describe the first clinical A. fumigatus strain with this resistance mechanism isolated from an Argentinian patient. The strain was isolated in 2009 (1 year after the first-described mutant in United States), demonstrating that these alleles were scattered worldwide earlier than previously thought.